Changes in keratin 8/18 expression in human granulosa cell lineage are associated to cell death/survival events: potential implications for the maintenance of the ovarian reserve. Issue 4 (1st February 2018) - Gaytan, F; Morales, C; Roa, J; Tena-Sempere, M
Abstract: STUDY QUESTION: Is keratin 8/18 (K8/K18) expression linked to cell death/survival events in the human granulosa cell lineage? SUMMARY ANSWER: A close association exists between changes in K8/K18 expression and cell death/survival events along the human granulosa cell lineage lifespan. WHAT IS KNOWN ALREADY: In addition to their structural and mechanical functions, K8/K18 play essential roles regulating cell death, survival and differentiation in several non-gonadal epithelial tissues. Transfection of the granulosa-like tumor KGN cells with siRNA to interfere KRT8 and KRT18 expression increases FAS-mediated apoptosis, while an inverse association between K8/K18 expression and cell death has been found in the bovine antral follicles and corpus luteum. Yet, only fragmentary and inconclusive information exists regarding K8/K18 expression in the human ovary. STUDY DESIGN, SIZE, DURATION: Expression of K8/K18 was assessed by immunohistochemistry at different stages of the granulosa cell lineage, from flattened granulosa cells in primordial follicles to fully luteinized granulosa-lutein cells in the corpus luteum (including corpus luteum of pregnancy). PARTICIPANTS/MATERIALS, SETTING, METHODS: Immunohistochemical detection of K8/K18 was conducted in 40 archival ovarian samples from women aged 17–39 years. K8/K18 expression was analyzed at the different stages of follicle development and corpus luteum lifespan. The proportions of primordial follicles showing all K8/K18-positive, all K8/K18 negative, or a mixture of K8/K18 negative and positive granulosa cells were quantified in 18 ovaries, divided into three age groups: ≤ 25 years ( N = 6), 26–30 ( N = 6) and 31–36 ( N = 6) years. A total number of 1793 primordial, 750 transitional and 140 primary follicles were scored. MAIN RESULTS AND THE ROLE OF CHANCE: A close association was found between changes in K8/K18 expression and cell death/cell survival events in the human granulosa cell lineage. Large secondary and early antral follicles (most of them undergoing atresia) and regressing corpora lutea displayed low/absent K8/K18 expression. Conversely, early growing and some large antral follicles, functional menstrual corpora lutea, as well as life-extended corpus luteum of pregnancy, in which cell death was scarce, showed high K8/K18 expression. Three sub-populations of primordial follicles were observed with respect to the presence of K8/K18 in their flattened granulosa cells, ranging from primordial follicles showing only positive granulosa cells [P0(+)], to others with a mixture of positive and negative cells [P0(+/−)] or follicles with only negative cells [P0(−)]. Significant age-related changes were found in the proportions of the different primordial follicle types. In relation to age, a positive correlation was found for P0(+) primordial follicles ( R 2 = 0.7883, N = 18; P < 0.001), while negative correlations were found for P0(+/−) ( R 2 = 0.6853, N = 18; P < 0.001) and P0(−) ( R 2 = 0.6725, N = 18; P < 0.001) follicles. Furthermore, an age-related shift towards greater keratin expression was found in P0(+/−) follicles ( χ 2 = 19.07, P < 0.05). LARGE SCALE DATA: N/A. LIMITATIONS REASONS FOR CAUTION: This is a descriptive study. Hence, a cause-and-effect relationship between K8/K18 expression and cell death/survival cannot be directly established. WIDER IMPLICATIONS OF THE FINDINGS: This study describes, for the first time, the existence of sub-populations of primordial follicles on the basis of K8/K18 expression in granulosa cells, and that their proportions change with age. While a progressive increase in K8/K18 expression cannot be ruled out, our data are consistent with the hypothesis that primordial follicles expressing low levels of K8/K18 are preferentially ablated by follicle attrition, while primordial follicles showing high K8/K18 levels are those predominantly recruited into the growing pool. This suggests that K8/K18 expression could constitute a novel factor regulating primordial follicle death/survival, and raises the possibility that alterations of K8/K18 expression could be involved in the accelerated depletion of the ovarian reserve leading to premature ovarian insufficiency. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by Grants BFU2011-025021 and BFU2014-57581-P (Ministerio de Economía y Competitividad, Spain; co-funded with EU funds from FEDER Program); project PIE14-00005 (Flexi-Met, Instituto de Salud Carlos III, Ministerio de Sanidad, Spain); Projects P08-CVI-03788 and P12-FQM-01943 (Junta de Andalucía, Spain); and EU research contract DEER FP7-ENV-2007-1. CIBER Fisiopatología de la Obesidad y Nutrición is an initiative of Instituto de Salud Carlos III. The authors have nothing to disclose in relation to the contents of this study.